Checklist for the Structural Description of the Deep Phenotype in Disorders of Sexual Development - L. Wünsch (International Journal of Endocrinology)
This paper addresses the question, how the variations of the deep phenotype in disorders of sex development (DSD) are appropriately described. This is a relevant question, because extensive phenotypic variability occurs in gonads and sex ducts. With the advance of video endoscopy and laparoscopy, fresh insight in gonadal and sex duct anatomy is emerging. So far, an attempt to standardize the diagnostic approach and, in particular, how to document these findings has not been published. We propose a standardized examination schedule for these procedures. It consists of 5 pictures of relevant anatomic features. For laparoscopy, it includes two pictures each of gonads and sex ducts on either side and an image of the retrovesical space. For endoscopy, the examination of the ureteric orifices, the posterior urethra, and the urogenital sinus derivates is recommended. Adherence of a standardized schedule and image storing enhances patient autonomy, because they can carry their examination for a second opinion without need for repeated examination. Physicians and scientists create a structured image library that facilitates the comparison of clinical outcomes, research on genotype phenotype associations and may lead to better classifications.